Untersuchungen zum Vorkommen von aviären Influenza- und aviären Paramyxoviren bei Wildvögeln in Deutschland - Globig, Anja (Tierärztliche Hochschule, 2007)
Wild birds, particularly belonging to the orders Anseriformes and Charadriiformes are known as a major reservoir for low pathogenic avian influenza- (LPAIV) and paramyxoviruses (APMV). In recent outbreaks of highly pathogenic avian influenza (HPAI) and Newcastle Disease (ND), it was shown that wild birds played a role in transmission of virus into poultry farms. In order to determine the current prevalence of AIV and APMV in wild birds in Germany and to assess the potential risk for poultry, extensive surveillance studies were carried out between March 2003 and November 2005. In cooperation with the Hiddensee bird ringing centre, voluntary bird ringers, hunters and other volunteers 3.672 cloacal swab samples of 78 wild bird species out of eleven orders with focus on waterfowl of the orders Anseriformes and Charadriiformes were collected, partly pooled and investigated. Samples were taken from migratory as well as from resident birds from 80 regions of 12 different federal stats of Germany. In total 105 haemagglutinating isolates could be obtained, of which 53 were characterized as AIV and 52 as APMV. Among the AIV the subtypes H1N1, H2N2, H2N3, H3N2, H3N8, H4N6, H5N2, H5N3, H6N2, H7N1, H7N7, H10N4, H10N7, H11N9 could be isolated from Mallards, (Anas plathyrhynchos), H4N6, H5N1, H5N2, H7N2, H7N7 from Teals (Anas crecca), H6N? from a Wigeon (Anas penelope), H13N6 from a Herring gull (Larus argentatus) and Jackdaw (Corvus monedula) and H10N4 from a Moorhen (Gallinula chloropus). APMV-1 were obtained from Mallards and Teals, a coot (Fulicula atra), a Black-headed gull (Larus ridibundus) and Mute swans (Cygnus olor), APMV-4 from Mallards, Teals and Wigeons, a Black-headed gull and Magpie (Pica pica), APMV- 6 from Mallards, a Mute swan and a Greylag goose (Anser anser) and APMV-9 from Mallards. There was a considerable variability noted among species, season and location. All AIV were isolated from birds sampled in autumn and early winter, whereas APMV was also found to other seasons. Most of the AIV isolates came ...